2009
DOI: 10.1111/j.1744-7917.2009.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses of Aphidius gifuensis to odors of host plants and aphid‐plant complexes

Abstract: The olfactory responses of Aphidius gifuensis to odors from two host plants (Nicotiana tabacum and Brassica napus ssp.) and their complexes with different infestation levels of two host aphids (Myzus persicae and Lipaphis erysimi) were respectively examined in an olfactometer. The results showed that female A. gifuensis did not respond to odors of undamaged or mechanically damaged host plants, but significantly responded to odors of aphid/plant complexes. Moreover, A. gifuensis responded significantly to odors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Our results indicated that the aphidinduced tomato volatiles not only attracted an aphid parasitoid, but also two whitefly parasitoids. A similar result was obtained by Yang et al (2009) with plants infested with either M. persicae or L. erysimi; these authors speculated that the quantity of aphid-induced plant volatiles may be important. Our results demonstrated that the aphid parasitoid A. gifuensis was most attracted to high aphid densities.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results indicated that the aphidinduced tomato volatiles not only attracted an aphid parasitoid, but also two whitefly parasitoids. A similar result was obtained by Yang et al (2009) with plants infested with either M. persicae or L. erysimi; these authors speculated that the quantity of aphid-induced plant volatiles may be important. Our results demonstrated that the aphid parasitoid A. gifuensis was most attracted to high aphid densities.…”
Section: Discussionsupporting
confidence: 70%
“…Our results demonstrated that the aphid parasitoid A. gifuensis was most attracted to high aphid densities. A similar result was obtained by Yang et al (2009) with plants infested with either M. persicae or L. erysimi; these authors speculated that the quantity of aphid-induced plant volatiles may be important. Specialist parasitoids often use very specific compounds released from the host plant (Steidle & van Loon, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Our results suggest that both natural enemies are able to rapidly locate aphid colonies, which would benefit the effectiveness of these two natural enemies. Since the amounts of volatiles produced by the plant/aphid complex will increase with time as the aphid colonies increase in size, attraction of A. ervi and A. aphidimyza to the aphid-infested plants will probably increase, as has been demonstrated for Aphidius gifuensis (Ashmead) (Hymenoptera: Braconidae) (Yang et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The endoparasitoid, Aphidius gifuensis (Ashmead), is one of the most important natural control agent for S . avenae on wheat [ 33 – 34 ]. So, we hypothesize that S .…”
Section: Introductionmentioning
confidence: 99%